2005
DOI: 10.1002/chem.200500332
|View full text |Cite
|
Sign up to set email alerts
|

Gaseous HgH2, CdH2, and ZnH2

Abstract: Gaseous HgH2, CdH2, and ZnH2 molecules were synthesized by the direct gas-phase reaction of excited mercury, cadmium, and zinc atoms with molecular hydrogen. The molecules were identified by their high-resolution infrared emission spectra, and the metal-hydrogen bond lengths were determined from the rotational analysis of the antisymmetric stretching fundamental bands.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
37
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 33 publications
1
37
0
Order By: Relevance
“…Although the existence of solid mercury dihydride (HgH 2 ) has been known for more than half a century [1,2], it was only recently that molecular HgH 2 could be investigated by means of highresolution spectroscopy [3,4]. Gaseous HgH 2 and its deuterated isotopomers were synthesized through the reaction of mercury vapour with molecular hydrogen or deuterium in the presence of a dc electrical discharge.…”
Section: Introductionmentioning
confidence: 99%
“…Although the existence of solid mercury dihydride (HgH 2 ) has been known for more than half a century [1,2], it was only recently that molecular HgH 2 could be investigated by means of highresolution spectroscopy [3,4]. Gaseous HgH 2 and its deuterated isotopomers were synthesized through the reaction of mercury vapour with molecular hydrogen or deuterium in the presence of a dc electrical discharge.…”
Section: Introductionmentioning
confidence: 99%
“…The same authors [102] concluded that the relative stability of gaseous HgH 2 , CdH 2 , and ZnH 2 molecules supports the hypothesis that these species are formed during the reduction of aqueous Hg, Cd, and Zn ions in the "hydride generation" technique. However, simple binary metal hydrides are solid.…”
Section: Mechanism Of Chg Of Transition and Noble Metalsmentioning
confidence: 75%
“…For Hg 2+ , the well-known reaction giving Hg 0 can be written as [102][103][104]. The same authors [102] concluded that the relative stability of gaseous HgH 2 , CdH 2 , and ZnH 2 molecules supports the hypothesis that these species are formed during the reduction of aqueous Hg, Cd, and Zn ions in the "hydride generation" technique.…”
Section: Mechanism Of Chg Of Transition and Noble Metalsmentioning
confidence: 94%
“…Gaseous ZnH 2 , CdH 2 , and HgH 2 molecules have been discovered recently in our laboratory at the University of Waterloo, and their infrared emission spectra were recorded at high resolution using a Fourier transform spectrometer [1][2][3][4][5]. These spectra also contained a few vibration-rotation bands of ZnH, ZnD, CdH, and CdD in the X 2 R + ground state, which are described in this paper.…”
Section: Introductionmentioning
confidence: 96%